UN Women's evaluation of the SDGs: what is the role for the CGIAR? - Sijapati-Basnett, Bimbika (Center for International Forestry Research, 2018)
Presented by Bimbika Sijapati-Basnett (CIFOR), as part of the Gender Research Coordinators' meeting (24 September 2018) ahead of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research. The latter event took place on 25-27 September 2018 in Addis Ababa, Ethiopia, hosted by the International Livestock Research Institute (ILRI) and co-organized with KIT Royal Tropical Institute.